Aspectos clínicos e funcionais em trabalhadores ativos com e sem sintomas ou evidências de DORT - Walsh, Isabel Aparecida Porcatti de (2004)
Work-related musculoskeletal disorders (WRMDs) are diseases that result in persistent pain, loss of functional capacity and associated work disability. This diagnostic is important because it is used to guide clinical and legal decisions. Their initial diagnosis is difficult because such diagnoses are based on complaints of pain and they often involve conflicting social and economic interests. Because of the complexity of such diagnoses, further studies are needed in order to analyze the association between subjective descriptions and objective findings. Therefore was made two research. The objective of the first research was to evaluate the impact of personal, clinical and occupational aspects on work ability of workers with and without WRMDs using an approved version of the Work Ability Index (WAI) and pain scale. This evaluated 127 workers of industrial production lines. A descriptive analysis was carried out using the Chi-square test and it was also performed a logistic regression analysis. A significant association was identified between the WAI and all personal, clinical and occupational aspects. Regression analysis showed that pain and sick leave together accounted for 59% of poor work ability. The objective of the second research was to evaluate the clinical and functional aspects of WRMDs, in relation to physical evaluation, perception of pain, self-reporting of symptoms and functional ability, among active workers at a single company with and without symptoms or evidence of this disorders. 134 female workers were physically evaluated by two trained physiotherapists. They filled out a questionnaire on discomfort due to pain, a pain scale, the Oswestry Disability Questionnaire (ODQ) and the Work Ability Index (WAI). The results were correlated and logistic regressions were run. According to the results symptom reports were explained by the results from the pain scale and the clinical findings and clinical findings by symptom reports and WAI. In two research the relationship between pain, symptom reports and clinical findings demonstrates that the patient s current state can be assessed not only by means of objective examinations, but also by means of instruments that take into account the patient s perception of his or her state.